2000
DOI: 10.1074/jbc.275.2.1384
|View full text |Cite
|
Sign up to set email alerts
|

Post-translational Proteolytic Processing of Procollagen C-terminal Proteinase Enhancer Releases a Metalloproteinase Inhibitor

Abstract: Activity of matrix metalloproteinases (MMP) is regulated by a family of proteins called tissue inhibitors of metalloproteinases (TIMP). Four TIMPs have been cloned, and their molecular weights range from 29,000 to 20,000. By reverse zymography, we have observed a metalloproteinase inhibitor with an apparent molecular weight of 16,500 from medium conditioned by human brain tumor cells. Antibodies directed against TIMPs failed to react with the 16,500 molecular weight inhibitor, indicating that it was not a trun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
86
1
10

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 119 publications
(100 citation statements)
references
References 42 publications
(29 reference statements)
3
86
1
10
Order By: Relevance
“…Because the NTR domains of TIMPs are responsible for their metalloprotease inhibitory activity, we have suggested that NTR modules might be involved in controlling the activity of zinc metalloproteases (1). Our prediction that the NTR module of PCOLCE may be a metalloprotease inhibitor has been confirmed by recent experiments (2).…”
supporting
confidence: 70%
“…Because the NTR domains of TIMPs are responsible for their metalloprotease inhibitory activity, we have suggested that NTR modules might be involved in controlling the activity of zinc metalloproteases (1). Our prediction that the NTR module of PCOLCE may be a metalloprotease inhibitor has been confirmed by recent experiments (2).…”
supporting
confidence: 70%
“…Sfrps, TIMPs and PCOLCEs share similarities in the NTR domain which, in TIMP and POLCE is thought to interfere with protease activity 44 . The structure of ADAM10 comprises, adjacent to the catalytic and disintegrin domains, a cysteine-rich motif, which is thought to mediate interaction with other molecules 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, PCOLCEs may act via forming a ternary complex between the most carboxyl-terminal domains of BMP1/TLD-like proteinases and their procollagen substrates. The PCOLCE1 NTR domain possesses inhibitory activity against MMPs, and perhaps other proteinases (Mott et al, 2000), and thus may play some role as an inhibitor of collagen catabolism. PCOLCE1-null mice have profoundly abnormal collagen fibrils in both bone and soft tissues, suggesting that PCOLCE1 may play additional in vivo roles beyond enhancement of pCP acitivity .…”
Section: Procollagen C-proteinase Enhancersmentioning
confidence: 99%